2019
DOI: 10.31080/aspe.2019.02.0187
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Professionals Use of Mobile Phones in the Operating Theatre

Abstract: Mobile phones are a normal companion in our everyday life.They are taken for granted to an extent that it is common that healthcare professionals use mobile phones for both professional and personal issues in the workplace [2,5,20,28,29] and younger employees tend to use private cell phones more often than older [7,17,19,20]. It has been reported that more than 78 percent of healthcare professionals use their private mobile phones at work [3,5,7,17,20,25,32]. However, the healthcare professionals find it diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…41 Results of a study involving 33 participants showed that 9 (27.3%) found cell phone use in the OR to be distracting every day. 15 Because respondents in our study mainly used the mobile phone for private purposes, our results may indicate that the respondents may have found other team members' use of cell phones distracting, or that they found responding to surgeons' calls distracting.…”
Section: Perceptions On Cell Phone Usementioning
confidence: 84%
See 4 more Smart Citations
“…41 Results of a study involving 33 participants showed that 9 (27.3%) found cell phone use in the OR to be distracting every day. 15 Because respondents in our study mainly used the mobile phone for private purposes, our results may indicate that the respondents may have found other team members' use of cell phones distracting, or that they found responding to surgeons' calls distracting.…”
Section: Perceptions On Cell Phone Usementioning
confidence: 84%
“…In a variety of pediatric settings, 80% of cell phone use was work related 24 . Additional study results showed that 18 (54.5%) of 33 perioperative respondents indicated that they used cell phones in the OR for personal reasons, 15 and 644 (78.1%) of 825 medical‐surgical nurses used their phones during work for personal reasons 35 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations